Penghentian Perkara Berdasarkan Restorative Justice Dalam Perkara Tindak Pidana Pencurian Di Kota Sorong - Ramli, Irfan; Hidaya, Wahab Aznul; Muharuddin, Muharuddin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The main point of this problem is to find out how the process of handling restorative justice in theft crimes at the Sorong State Prosecutor's Office. This research uses emperical research methods by combining existing data in the field and those related to what is discussed in this thesis. The result of this thesis research is to explain or discuss related to theft crimes that can be solved by the process of restorative justice. The conclusion of this study is that the termination based on restorative justice for how to fight to encourage someone who commits a criminal case not to undergo criminal proceedings through joint deliberation is expected to provide a solution and alternative resolution of criminal cases.